Intracardiac Teratoma in an Infant: Report of a New Case and Literature Review - Mustapha Azzakhmam; Amine Kessab; Abderrahmane Malihy; Lamiae Rouas; Najat Lamalmi (Hindawi Limited, 2018)
Primitive intracardiac tumours are rare, especially in childhood, and are often discovered on autopsy. The intracardiac teratoma is the rarest intracardiac tumours of childhood. Herein, we report the case of an 11-month-old infant, which featured recurrent bronchoalveolitis since the age of 3 months, with a thoracic deformation. Physical examination did found discrete respiratory distress signs. Chest radiography showed large mediastinal enlargement. The computed tomography showed a solid cystic-cloisonned mass with fat and central calcification highly suggestive of an intracardiac teratoma. A radical surgical excision was made and the histological examination found a well circumscribed tumour containing elements of the three germ layers confirming the diagnosis of mature well-differentiated teratoma, with no need of immunohistochemical support.